ENHANCED SCHOOL-BASED CAFETERIA SERVICES GUIDE IN A TECHNOLOGICAL UNIVERSITY - Tamayo, Daisy Gepitulan (Journal of Agriculture and Technology Management; Vol 26 No 2 (2023): Vol 26 No 2 (2023): Journal of Agriculture and Technology Management (JATM) Volume 26 July - December 2023 Issue, 2023)
This study assessed the cafeteria services at Cebu Technological University during the Academic Year 2015-2016 as bases to formulate an enhanced school-based cafeteria services guide.  This study was conducted on all CTU campuses:  Argao, Barili, Carmen, Camotes, Daan-Bantayan, Danao, Main, Moalboal, and Tuburan Campus.  The respondents were the 48 cafeteria personnel and 143 students.  This research utilized the descriptive method, and the main instrument used in obtaining data was the questionnaire.  The data were treated and gathered using simple percentages and weighted mean and were subject to statistical treatment.  The majority of the Cafeteria Personnel belonged to the age bracket of 21-50 years, males and single.  Despite the lack of service personnel, all the campuses had personnel who were very courteous and polite.  They gave equal treatment to the students, employees, and teachers.  They also provide services during the schools’ student affairs, efficient and patient when responding to the complaints or needs of the clientele.  Hiring more personnel and letting them undergo proper training and seminars is recommended.  Improve the equipment and facilities of the school canteens on the campuses.  It should be updated with modern technology that could be used in the cafeteria.  And to follow the enhanced school-based cafeteria services guide to develop and improve the management of the cafeteria in the schools and universities in the system.